2018
DOI: 10.1016/j.jand.2017.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Family Home Food Environment and Nutrition-Related Parent and Child Personal and Behavioral Outcomes of the Healthy Home Offerings via the Mealtime Environment (HOME) Plus Program: A Randomized Controlled Trial

Abstract: The Healthy Home Offerings via the Mealtime Environment Plus program involved the entire family and targeted personal, behavioral, and environment factors important for healthful changes in the home food environment and children's dietary intake. The intervention improved two nutrition-related behaviors and this may inform the design of future family meal interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
76
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(89 citation statements)
references
References 71 publications
8
76
0
5
Order By: Relevance
“…This is particularly true for interventions that target the home rather than school environment [ 71 ]. Interventions aimed at teaching parents of school-aged children to set goals for making health-related behavior changes for their families can be effective at reducing children’s SSB consumption [ 72 ]. The success of these interventions is congruent with some recommendations in Table 1 , including facilitating behavior change by adjusting the home environment and building parent self-efficacy for making behavior changes.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly true for interventions that target the home rather than school environment [ 71 ]. Interventions aimed at teaching parents of school-aged children to set goals for making health-related behavior changes for their families can be effective at reducing children’s SSB consumption [ 72 ]. The success of these interventions is congruent with some recommendations in Table 1 , including facilitating behavior change by adjusting the home environment and building parent self-efficacy for making behavior changes.…”
Section: Discussionmentioning
confidence: 99%
“…The models for maternal dietary intake predictors were adjusted for maternal child feeding and nutrition knowledge and maternal education [ 41 ]. The models for home food availability predictors were adjusted for maternal child feeding and nutrition knowledge and maternal education [ 42 ]. The model for predictor maternal education had no additional adjustments; 3 all bolded results show significant associations ( p ≤ 0.05).…”
Section: Tablementioning
confidence: 99%
“…Other intervention studies have targeted changes to the home environment as a way to promote behavior change ( 14 , 45 ). Gorin et al ( 14 ) found that an intervention which included a behavioral component as well as a home environment focused intervention had benefits on the home environment as well as a stronger impact on weight loss at 6 months compared with a group that received only the behavioral component.…”
Section: Discussionmentioning
confidence: 99%
“…While only one home environment factor was significantly impacted by the intervention, qualitative research has indicated even small changes can be challenging to implement ( 46 ). Further, other intervention trials have been efficacious in terms of modifying some home environment characteristics but not others ( 44 , 45 ).…”
Section: Discussionmentioning
confidence: 99%